Nonlinear Wave Making Resistance Calculation for Large Ships in Restricted Waterways - Zhao, Xin; Zhang, Xujin (Informatica, 2024)
With the prosperous development of the maritime transportation industry, the application of large ships is becoming more frequent. However, large ships are greatly affected by wave making during navigation. The current calculation model for wave making resistance of large ships is not effective. To improve the overall performance of the calculation model for wave making resistance of large ships, a hybrid optimization algorithm is first obtained by combining the firefly algorithm and the squirrel search algorithm. Then, a new ship wave making resistance calculation model is constructed based on the hybrid optimization algorithm and computational fluid dynamics. In the performance comparison of hybrid optimization algorithms, the F-value and G-value were 85.2% and 92.3%, respectively, significantly better than the comparison algorithms. Subsequently, a comparative experiment was conducted on the ship wave resistance calculation model. The results showed that the average memory consumption and error value of the proposed model were 883.3 Mb and 0.0086, respectively, which were significantly better than comparison algorithms. The above results indicate that the proposed wave resistance calculation model can effectively calculate the resistance value of nonlinear wave making for large ships in restricted waterways. Therefore, this study is of great significance for promoting the development of the maritime transportation industry.